Characterization of Fusarium graminearum isolates recovered from wheat samples from Argentina by Fourier transform infrared spectroscopy : phenotypic diversity and detection of specific markers of aggressiveness - Fígoli, Cecilia Beatriz (2017)
Fusarium graminearum is the primary causal agent of Fusarium head blight of wheat in Argentina. This disease affects crop yields and grain quality also reducing the wheat end-use, and causing mycotoxin contamination. The aim of this work was to analyze the phenotypic characteristics associated with phenotypic diversity and aggressiveness of 34 F. graminearum sensu stricto isolates recovered from Argentinean fields in the 2008 growing season using the Fourier Transform Infrared (FTIR) dried film technology. We applied this technique also to search for spectral specific markers associated with aggressiveness. The combination of FTIR technology with hierarchical cluster analysis allowed us to determine that this population constitutes a highly diverse and heterogeneous group of fungi with significant phenotypic variance. Still, when the spectral features of a set of these isolates were compared against their aggressiveness, as measured by disease severity, thousand grains weight, and relative yield reduction, we found that the more aggressive isolates were richer in lipid content. Therefore, we could define several spectroscopic markers (NC\\H stretching modes in the 3000–2800 window, NC_O and\\C\\O vibrational modes of esters at 1765–1707 cm−1 and 1474–900 cm−1, respectively), mostly assigned to lipid content that could be associated with F. graminearum aggressiveness. All together, by the application of FTIR techniques and simple multivariate analyses, it was possible to gain significant insights into the phenotypic characterization of F. graminearum local isolates, and to establish the existence of a direct relationship between lipid content and fungal aggressiveness. Considering that lipids have a major role as mediators in the interaction between plants and fungi our results could represent an attractive outcome in the study of Fusarium pathogenesis.